Treatment decisional regret among men with prostate cancer: Racial differences and influential factors in the North Carolina Health Access and Prostate Cancer Treatment Project (HCaP‐NC). Issue 12 (3rd March 2015) - Morris, Bonny B.; Farnan, Laura; Song, Lixin; Addington, Elizabeth L.; Chen, Ronald C.; Nielsen, Matthew E.; Mishel, Merle; Mohler, James L.; Bensen, Jeannette T.
<x xml:space="preserve">Abstract</x> BACKGROUND It has been demonstrated that treatment decisional regret affects quality of life in patients with prostate cancer (CaP); however, there are limited studies that identify factors associated with treatment decisional regret, particularly within a racially diverse patient population that has extended follow‐up. METHODS Logistic regression analysis was used to determine associations between decisional regret and potential predictors in a population‐based cohort of 348 African American men and 446 Caucasian American men approximately 3 years after CaP diagnosis. RESULTS Of 794 research participants, 12% experienced treatment decisional regret. Decisional regret was associated with androgen‐deprivation therapy (odds ratio [OR], 2.1; 95% confidence interval [CI], 1.1‐4.0), recent urinary bother (OR, 3.4; 95% CI, 1.6‐7.3), satisfaction with understanding potential treatment side effects (very unsatisfied: OR, 13.3; 95% CI, 5.5‐32.2; somewhat unsatisfied: OR, 5.0; 95% CI, 2.3‐11.2; neutral: OR, 3.8; 95% CI, 1.9‐7.6), and CaP treatment effect on the spousal relationship (very affected: OR, 3.9; 95% CI, 2.0‐7.6; somewhat affected: OR, 3.1; 95% CI, 1.4‐7.3; neutral: OR, 2.4; 95% CI, 1.9‐7.6). Younger African Americans were more likely to experience regret than older African Americans (OR, 3.0; 95% CI, 1.1‐8.1), and older African Americans were less likely to experience regret than older Caucasian Americans (OR, 0.2; 95% CI, 0.1‐0.7). CONCLUSIONS Treatment decisional regret remains an important issue in CaP survivors beyond initial treatment. Potential interventions should involve younger African Americans and patient spouses. Increased regret may reflect the unexpected influence of treatment side effects on the patient's everyday life; helping the patient relate potential side effects to his individual situation could improve patient satisfaction. Cancer 2015;121:2029–2035. © 2015 American Cancer Society.